Kududukan Doi Menre dalam Perkawinan Suku Bugis di Bone Sulawesi Selatan - Amri, Reski Ulul (UIN Sunan Kalijaga, 2020)
Abstract: Doi menre is the giving of a sum of money by the prospective husband to the prospective wife under the agreement between the two families for the spent of the wedding party. Doi menre frequently decisively affects whether the marriage process will proceed. This paper aims to explain how the position and impact of Doi menre in Bugis marriages, Bone Regency. This research is a field study. Data were collected through interviews, then analyzed qualitatively. Based on the research, it can be concluded that Doi menre in the traditional marriage of the Bugis Bone community has been preserved as one of the primary requirements for marriage in the Bugis Bone community. Arguably marriage will not take place without Doi menre. This is different according to Islamic law, which stipulates that Doi menre is not part of the conditions that must be met. Thus, the position of Doi menre has become the customary law of the Bugis Bone community.Abstrak: Doi menre adalah pemberian sejumlah uang oleh pihak laki-laki (calon suami) kepada calon isteri sesuai dengan kesepakatan kedua belah keluarga untuk keperluan pesta perkawinan. Doi menre sering menjadi penentu berlangsung tidaknya perkawinan. Tulisan ini bertujuan menjelaskan bagaimana kedudukan dan dampak Doi menre dalam perkawinan adat suku Bugis di Kabupaten Bone. Penelitian ini adalah penelitian lapangan. Data dikumpulkan dengan cara wawancara, kemudian dianalisis secara kualitatif. Berdasarkan penelitian, dapat disimpulkan bahwa Doi menre dalam perkawinan adat masyarakat Bugis Bone telah menjadi syarat utama perkawinan sesuatu yang harus ada. Perkawinan tidak akan terlaksana tanpa Doi menre dari pihak laki-laki. Hal ini berbeda meurut Hukum Islam bahwa Doi menre tidak termasuk bagian dari syarat yang harus terpenuhi. Dengan demikian kedudukan Doi menre telah menjadi hukum adat masyarakat Bugis Bone.